Combining Neprilysin Inhibitor With AT2R Agonist Is Superior to Combination With AT1R Blocker in Providing Reno-Protection in Obese Rats - Gray, Elizabeth Alana; Patel, Sanket N.; Doris, Peter A.; Hussain, Tahir (Frontiers in Pharmacology, 2022)
Clinical use of the combination therapy of the neprilysin inhibitor sacubitril and angiotensin II type 1 receptor blocker valsartan is known to be associated with albuminuria. Albuminuria is both a risk factor for and an indicator of kidney injury. Earlier work from our laboratory reported that the agonist of angiotensin II type 2 receptor Compound 21 (C21) prevents proteinuria, albuminuria, and is reno-protective in obese Zucker rats fed high salt diet (HSD). Thus, we hypothesized that sacubitril/C21 combination provides superior reno-protection compared to sacubitril/valsartan. Male obese Zucker rats 10–11 weeks old were treated daily with vehicle, sacubitril + C21, or sacubitril + valsartan while fed HSD for 16 days. HSD-feeding caused kidney dysfunction, evident by significant increases in urinary protein, osteopontin, and cystatin C. HSD-feeding lowered plasma cystatin C and creatinine concentrations suggestive of hyperfiltration, which was not affected by either treatment. Unlike sacubitril/valsartan, sacubitril/C21 treatment significantly decreases proteinuria, albuminuria, the expression of nephrin, and kidney weight, independent of hyperfiltration, compared with HSD alone. Moreover, sacubitril/valsartan therapy increased plasma renin and did not prevent HSD-induced increases in renal angiotensin II, while sacubitril/C21 completely prevented these changes. Together, this study suggests that sacubitril/C21 afforded superior reno-protection compared to sacubitril/valsartan therapy in high salt-fed obese Zucker rats.